Polski Współczynnik Wpływu a kultury cytowań w humanistyce - Drabek, Aneta; Rozkosz, Ewa A.; Hołowiecki, Marek; Kulczycki, Emanuel (My University, 2015)
The article discusses the formula for a new Polish bibliometric indicator, i.e., the Polish Impact Factor (Polski Współczynnik Wpływu) from the point of view of the humanities. Our study examines two prestigious Polish humanities journals (Pamiętnik Literacki and Diametros – An Online Journal of Philosophy) to evaluate the underlying assumptions of the Polish Impact Factor. We have analyzed all articles published from 2004 to 2014 (N = 850, N = 555, respectively) and all references included in these articles (N = 21,805, N = 8,298, respectively). When interpreting the findings, we have assumed that different groups of sciences are characterized by different citation cultures. Our findings show that the formula for the Polish Impact Factor does not take into account the most cited sources in the humanities, i.e., books and chapters. Moreover, many citations will not be included in the formula because of the citation age: the formula for the Polish Impact Factor is provided for the citations whose age is not higher than 5 years. We have analyzed the citation age of all citations and used Price’s Index to interpret the result. We have found out that most of citations are older than 5 years (84,2 percent and 73,2 percent, respectively). Our analysis shows that the Polish Impact Factor is not an adequate tool for a bibliometric evaluation of the journals in the humanities in Poland. The article concludes with a discussion of how the Polish Impact Factor could be improved.

W artykule omawiamy wzór na nowy polski wskaźnik bibliometryczny, tj. Polski Współczynnik Wpływu, z perspektywy nauk humanistycznych. Badaniom poddaliśmy dwa prestiżowe polskie czasopisma humanistyczne („Pamiętnik Literacki” i „Diametros – An Online Journal of Philosophy”), aby sprawdzić poprawność założeń przyjętych dla Polskiego Współczynnika Wpływu. Przeanalizowaliśmy wszystkie artykuły opublikowane w latach 2004–2014 (odpowiednio: N = 850, N = 555) i wszystkie prace w nich zacytowane (odpowiednio: N = 21 805, N = 8 298). W interpretacji wyników przyjęliśmy założenie o odmiennej kulturze cytowań w różnych grupach nauk. Wyniki pokazują, że wzór na Polski Współczynnik Wpływu nie bierze pod uwagę najczęściej cytowanych źródeł w humanistyce, tj. książek i rozdziałów. Poza tym wiele cytowań nie zostanie uwzględnionych przy wyliczaniu Polskiego Współczynnika Wpływu ze względu na ich wiek, ponieważ będą brane pod uwagę prace co najwyżej pięcioletnie lub nowsze. Zbadaliśmy wiek cytowanych tekstów i pokazaliśmy, że większość z cytowań jest starsza niż 5 lat (odpowiednio: 84,2% oraz 73,2%). Nasza analiza pokazuje, że Polski Współczynnik Wpływu nie jest odpowiednim narzędziem do bibliometrycznej oceny czasopism humanistycznych w Polsce. Artykuł kończy dyskusja nad możliwościami ulepszenia tego nowego wskaźnika bibliometrycznego.
Keywords: Polski Współczynnik Wpływu; kultura cytowań; bibliometria; wykaz czasopism punktowanych; Polish Impact Factor; scientometrics